US monetary policy spillovers to European banks - Alexander Jung (European Central Bank (ECB), 2023)
The Federal Reserve's (Fed) monetary policy announcements have created massive spillovers to global financial markets. Based on daily data for the sample from 1999 to 2019, this study finds that the Fed's monetary policy announcements created significant international spillovers to bond yields and stock prices of European banks and non-financial corporations (NFCs), while changes in uncertainty around the expected Fed policy path and Fed information effects constituted critical additional dimensions of these spillover effects. International spillovers to bond yields of banks and NFCs were similar, while stock prices of European banks responded somewhat stronger than those of NFCs. The significant spillovers from the Fed's forward guidance to European bond yields show that central bank communication is very relevant for international transmission. In relation to earlier studies emphasizing strong QE-related spillovers, this study suggests that Fed QE announcements created only small spillovers on bond yields and stock prices of European banks and NFCs.
Keywords: E44; E52; F42; G14; G21; 330; High-frequency event study; local projections; monetary policy shocks; monetary policy uncertainty; instrumental variables